Clinico-epidemiological study of oral squamous cell carcinoma: A tertiary care centre study in North India - Mahendra Pratap Singh; Vijay Kumar; Akash Agarwal; Rajendra Kumar; M.L.B. Bhatt; Sanjeev Misra (Journal of Oral Biology and Craniofacial Research)
Introduction: Oral squamous cell carcinoma (OSCC) ranks 12th most common cancer in the world. Objective: The aim of this study was to retrospectively evaluate the OSCC. Methods: A retrospective study of 611 OSCC patients from January 2010 to December 2013 was carried out in Department of Surgical Oncology, King George's Medical University, Lucknow, India. Details of patient's sex, age, tobacco habit and site of cancer were noted. Data were analyzed by Student's t test and chi-squire (χ2) test. Results: The prevalence of OSCC was significantly (p < 0.001) higher in males (75.9%) than females (24.1%). The mean age of female patients was higher than males (p < 0.001). In both the genders, the buccal mucosa and gingivobuccal sulcus were found to be the most affected sites. Moreover, the smokeless form of tobacco was found to be significantly associated with OSCC, especially in females. Conclusion: The study concluded that OSCC is more common in men as compared to women, probably due to habit of tobacco consumption. Smokeless tobacco use is an important risk factor, especially in females.